Socio-Economic Life In Tokharistan In The Early Middle Ages (Eurasian Journal of History, Geography and Economics, 2025)
This article provides a detailed account of the socio-economic life of Tokharistan in the early Middle Ages (5th-8th centuries) based on the analysis of written sources (Song Yun, Xiong Szan) and archaeological finds (Kofir Qala, Bolaliktepa, Ajinatepa, etc.). The article provides information on the development of agriculture, in particular, the importance of large irrigation structures such as the Kofir Canal, cultivated crops (grain, cotton, grapes) and livestock (Tokharistan horses). In the field of crafts, it is noted that stone mining (Badakhshan rubies), metalworking, jewelry, glassmaking (colored glass exported to China) and textiles (local development of silk production, luxury fabrics) were at a high level. The breadth of foreign and domestic trade relations, the export of thoroughbred horses, precious stones, medicinal products, and the internal circulation of copper coins indicate that Tokharistan was a civilization that achieved high economic development for its time.